Dionysius bar Ṣalībī: guardian of the Syriac Orthodox tradition - Jacobs, Bert; Teule, Herman G. B.; Verheyden, Joseph (Texts and studies in Eastern Christianity, 2025)
"Dionysius bar Salībī, a prominent 12th-century Syriac Orthodox bishop and scholar, played a key role in shaping Syriac Christian theology during a period of significant political upheaval in the eastern Mediterranean. His vast intellectual contributions spanned all major ecclesiastical disciplines of his time, including numerous theological works and scriptural commentaries. This volume brings together nine scholarly essays that explore his writings, theological insights, and his active role in both interreligious and intra-Christian debates. By examining his legacy, these studies highlight how Bar Ṣalībīboth consolidated and reshaped Syriac traditions to address the challenges of his era. The volume offers a wide range of perspectives on his enduring influence, underlining the significance of his multi-faceted contributions to Syriac Christianity"-- Provided by publisher